THE IMPORTANCE OF WATERWAYS IN TRADE AND ECONOMIC RELATIONS BETWEEN THE STATES OF UZBEKISTAN AND AFGHANISTAN - Dusmatova Oltinoy Tursun kizi (Journal of Learning on History and Social Sciences, 2024)
In this article, in the works of tourists, ambassadors, diplomatic officials, researchers of the 2nd half of the 19th-early 20th centuries, information on the issue of the establishment of trade and economic relations between the emirate of Bukhara and Afghanistan was studied and analyzed in detail.